The Impact of the Platform Economy on Job Creation - Willem Pieter De Groen; Zachary Kilhoffer; Karolien Lenaerts; Nicolas Salez (Intereconomics, 2017)
This study analysed the platform economy in terms of time, geography and type of platform, with a view to present estimations on its size in terms of revenues and the number of active workers.
Keywords: 330